Orientation in expected and unexpected landscapes – a case study of a newly established municipal healthcare unit - Hellen Dahl (International Practice Development Journal, 2020)
Background: This article examines how staff delivering care (two groups of healthcare workers and leaders) in a newly established unit worked to sustain required performance levels through changes and disruptions. It highlights discrepancies between plans for the unit (work as imagined) and reality in the unit (work as done).